Alda-1 Ameliorates Liver Ischemia-Reperfusion Injury by Activating Aldehyde Dehydrogenase 2 and Enhancing Autophagy in Mice - Meng Li; Min Xu; Jichang Li; Lili Chen; Dongwei Xu; Ying Tong; Jianjun Zhang; Hailong Wu; Xiaoni Kong; Qiang Xia (Journal of Immunology Research)
Aldehyde dehydrogenase 2 (ALDH2) is a key enzyme for metabolism of reactive aldehydes, but its role during liver ischemia-reperfusion injury (IRI) remains unclear. In the present study, we investigated the effects of the ALDH2 activator, Alda-1, in liver IRI and elucidated the underlying mechanisms. Mice were pretreated with Alda-1 and subjected to a 90 min hepatic 70% ischemia model, and liver tissues or serum samples were collected at indicated time points after reperfusion. We demonstrated that Alda-1 pretreatment had a hepatoprotective role in liver IRI as evidenced by decreased liver necrotic areas, serum ALT/AST levels, and liver inflammatory responses. Mechanistically, Alda-1 treatment enhanced ALDH2 activity and subsequently reduced the accumulation of reactive aldehydes and toxic protein adducts, which result in decreased hepatocyte apoptosis and mitochondrial dysfunction. We further demonstrated that Alda-1 treatment could activate AMPK and autophagy and that AMPK activation was required for Alda-1-mediated autophagy enhancement. These findings collectively indicate that Alda-1-mediated ALDH2 activation could be a promising strategy to improve liver IRI by clearance of reactive aldehydes and enhancement of autophagy.